STRATEGI BIMBINGAN AGAMA ISLAM DALAM MENCETAK SANTRI TELADAN DI PONDOK MODERN MASJID KURIR KELURAHAN SUMPANG BINANGAE KECAMATAN BARRU KABUPATEN BARRU (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This journal aims to describe how the strategy of Islamic religious guidance in producing exemplary students. This research uses descriptive qualitative research which is located in Pondok Modern Masjid Kurir Langit, Sumpang Binangae Village, Barru District, Barru Regency. The research approach used is the Islamic counseling guidance approach. The primary data sources for this research are Muhammad Amrullah the Leader of the Modern Pondok Courier Langit Mosque (key informant), additional informants are the Supervisor or Caretaker of the Modern Pondok Courier Sky Mosque and the Santriwan and Santriwati. Secondary data sources are books, theses, journals, literature, and other data sources that can be used as a complement. Data collection methods are observation, interviews, and documentation. Data analysis was carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the strategy of Islamic religious guidance in producing exemplary students at the Modern Islamic Boarding School of the Kurir Langit Mosque, Sumpang Binangae Village, Barru District, Barru Regency, there are three forms of methods, namely: individual guidance where the interaction technique between teachers and students in depositing memorization. The second script method (secret method) is that students are expected to be honest so that they can become exemplary students by filling out the habit checklist. Then, group guidance with the aim of being able to see significant differences between the students. The inhibiting factors are inadequate facilities and infrastructure, lack of teachers or human resources in the boarding school, as well as the intentions and mentality of the students. The solution is that it is hoped that the Modern Islamic Boarding School of the Courier Sky Mosque can add facilities and infrastructure in order to maximize guidance and learning in producing exemplary students.